Deep eutectic inks for multiphoton 3D laser microprinting - Mainik, Philipp; Spiegel, Christoph A.; Schneider, Jonathan L.G.; Wegener, Martin; Blasco, Eva (Advanced materials, 2025)
Multiphoton 3D laser printing of polymers has become a widespread technology for manufacturing 3D architectures on the micro- and nanometer scale, with booming applications in micro-optics, micro-robotics, and micro-scaffolds for biological cell culture. However, many applications demand material properties that are not accessible by conventional polymer inks. These include large stiffness, for which recent breakthroughs based on inorganic materials have been reported. Conversely, some applications require very low stiffness and high mechanical compliance. Existing solutions achieve softness by low crosslinking densities, at the inherent expense of deteriorated spatial resolution and structure quality. Herein, this apparent contradiction is resolved by introducing multiphoton inks based on deep eutectic systems, comprising Lewis or Brønsted acids/bases. The 3D printed materials support extremely large strains and bulk Young's moduli as low as 260 kPa under aqueous conditions, well suited for biological applications - at comparable ease of use and spatial resolution as well-established commercially available polymer inks.